Adrianus van Selms (1906–1984): What Does Abide? Aspects of his Life and Literary Contribution - Janse van Rensburg, Hans (Journal for Semitics, 2017)
<span style="line-height: 107%; font-family: 'Calibri',sans-serif; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-ZA; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Three decades have passed since the death of Adrianus Van Selms (22/1/1906â€“30/4/1984). He had become a legend in his own lifetime, and was even posthumously honoured at the centenary celebrations of the University of Pretoria as one of its hundred greatest academic achievers. But who was he? And what was his contribution in essence to the fields of Old Testament and Semitic languages? In this paper, an edited version of the SASNES Van Selms Memorial Lecture (September 2014), recollections of personal acquaintance with Van Selms, and impressions of others, are combined with a reflection based on archival material, a selection of his books, biblical commentaries and vast number of articles. Attention is given to his life (including controversies in which he was involved), his literary contribution, and particularly his analytical, comparative, and creative approach to the study of texts. Quite informative is a remark made by Van Selms (1967:50) in his book about northern Israel: â€œIn my scientific work I have always been alert to the power of my own imagination, but without the power of imagination no significant scientific work can be done.â€